Association of psychosocial stress with the social environment, lifestyle and risk factors for cardiovascular diseases in middle-aged male Muscovites - M. B. Kotova; V. B. Rozanov; A. A. Aleksandrov; O. M. Drapkina (Российский кардиологический журнал, 2021)
Aim. To study the relationship of psychosocial stress with the social environment, lifestyle and risk factors for cardiovascular diseases (CVDs) in middle-aged men.Material and methods. A total of 301 men aged 41-44 years were examined. The study included a clinical examination and a survey using a standard questionnaire. The categorization of CVD risk factors (RF) was carried out in accordance with generally accepted criteria. The psychosocial stress was assessed using the Reeder scale. Depending on the psychosocial stress level, all surveyed men were divided into 3 groups by tertiles: group 1 (3,28-4,0 points) — mild stress, group 2 (2,71-3,14) — moderate stress, group 3 (1,28-2,57) — severe stress.Results. More than half (53,5%) of males had manifestations of psychosocial stress, while 9% had a mild stress. With an increase in stress severity, the prevalence of hypertension increased and was significantly higher in men with a severe stress compared with their peers with mild stress (45,7% vs 31,7%; p=0,045). A significant linear trend was revealed between the levels of PSS and indicators of sedentary behavior. The strongest linear relationship was found between the psychosocial stress level and vital exhaustion (VE). The level of VE, stress at work, satisfaction with government performance and the level of family happiness are independent determinants of psychosocial stress level, and explain 33,1% of its variability. The proportion of the variance of psychosocial stress, uniquely explained by VE, is 20,8%, the absence of stress at work — 8,0%, satisfaction with government performance — 3,5% and the level of family happiness — 2,0%.Conclusion. A high level of psychosocial stress in middle-aged men is associated with hypertension, sedentary lifestyle and lower values of most indicators of the social environment, lifestyle and quality of life. This must be taken into account along with other behavioral and psychosocial risk factors for noncommunicable diseases when developing population-based programs.